ASPECTS RELATED TO CONDUCT OF ENVIRONMENTAL AUDIT - Misirov Komoliddin Mamasabirovich; Ganiev Shahriddin Vohidovich (PT ANTIS International Publisher, 2024)
This article covers aspects of environmental audit, ensuring environmental safety, reducing anthropogenic impact on the environment, eliminating environmental problems, and sustainable development of the country's economy